SOCIO POLITICAL THOUGHTS IN INDIAN JAIL LITERATURE - Afrin (International Journal of Multidisciplinary Research and Studies, 2021)
Modern society's responses to crime take many various forms and have a wide range of goals, all of which converge on crime control. In order to transform criminals and prevent them from committing crimes in the future, society needs to implement reformative practices, establish rehabilitative initiatives, and rehabilitate offenders. In jail, the "reformation" process might take place. Insofar as society desires defense against criminals. By separating criminals from society, the jail accomplishes this goal by preventing criminals from having the opportunity to harm society. The organization also anticipates reprisals The same and equal treatment must be given to offenders in prison since they have caused harm and made public life unpleasant. These are some of Robinson's goals for jail, to name a few. In the 18th century, the use of jail as a form of punishment replaced corporal punishment. The attitude of humanitarianism that emerged throughout the enlightenment is without a doubt one of the factors that contributed to the replacement of jail for physical and lethal punishment. People started to understand the horrors entailed in how society dealt with criminals. French thinkers like Voltaire pushed for improvements to the criminal justice system because they were shocked by what they dubbed "judicial murder." In the past, incarceration was used to punish people who had broken the law by causing them physical agony, much like the pound of flesh in Shakespeare's Merchant of Venice. In contrast to this idea, modern incarceration is now designed to focus on a person's intellect as well as his body through three main areas, including punishment, deterrence, and rehabilitation. These three distinct areas, when linked together into a single process, are meant to enable society to: remove criminals from a situation where they may continue their criminal behavior; place them in an institution that satisfies the masses' desire for some form of retribution; convince other potential criminals that such activities are not beneficial; and eventually mold them into productive and law-abiding citizens through positive psychological conditioning who may later be elected to public office.